2018
DOI: 10.1002/smll.201704465
|View full text |Cite
|
Sign up to set email alerts
|

Clay Nanoparticles Elicit Long‐Term Immune Responses by Forming Biodegradable Depots for Sustained Antigen Stimulation

Abstract: Nanomaterials have been widely tested as new generation vaccine adjuvants, but few evoke efficient immunoreactions. Clay nanoparticles, for example, layered double hydroxide (LDH) and hectorite (HEC) nanoparticles, have shown their potent adjuvanticity in generating effective and durable immune responses. However, the mechanism by which clay nanoadjuvants stimulate the immune system is not well understood. Here, it is demonstrated that LDH and HEC-antigen complexes form loose agglomerates in culture medium/ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 48 publications
1
57
0
Order By: Relevance
“…As demonstrated recently, clay nanoadjuvants with antigens loaded form a suitable nodule structure as a loose and soft depot in situ after subcutaneous injection. Compared with commercial adjuvant Alum, such nanocomplexes generate much looser agglomerates within nodules, where antigens are sustainably released and comparable immune cells are actively recruited for continuous immune stimulation over a long period (up to 21 d) …”
Section: Nanomaterials For Traditional and Novel Vaccine Deliverymentioning
confidence: 99%
“…As demonstrated recently, clay nanoadjuvants with antigens loaded form a suitable nodule structure as a loose and soft depot in situ after subcutaneous injection. Compared with commercial adjuvant Alum, such nanocomplexes generate much looser agglomerates within nodules, where antigens are sustainably released and comparable immune cells are actively recruited for continuous immune stimulation over a long period (up to 21 d) …”
Section: Nanomaterials For Traditional and Novel Vaccine Deliverymentioning
confidence: 99%
“…Engineering LDH nanoparticles for immunotherapy has gained increasing interests . Apart from being recognized as a competent vaccine carrier, recent studies have further unveiled the role of LDH itself as an excellent immunotherapeutic adjuvant …”
Section: Ldh Nanoparticles For Immunotherapymentioning
confidence: 99%
“…By synthesizing LDH with various compositions, Williams et al concluded that human DCs' response to LDH in vitro is highly correlated with a linear combination of three LDH properties: the radius of M 2+ (or M + ) metal cations, the interlayer spacing, and the surface charge . Chen et al proposed a so‐called depot effect to address the long‐term immune response provoked by LDH . LDHs formed loose aggregates and initiated the long‐term depot effect through slow degradation of LDH.…”
Section: Ldh Nanoparticles For Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations